The numerical solution of Newton’s problem of least resistance - Wachsmuth, Gerd (Mathematical programming, 2014)
In this paper we consider Newton’s problem of finding a convex body of least resistance. This problem could equivalently be written as a variational problem over concave functions in R 2 . We propose two different methods for solving it numerically. First, we discretize this problem by writing the concave solution function as a infimum over a finite number of affine functions. The discretized problem could be solved by standard optimization software efficiently. Second, we conjecture that the optimal body has a certain structure. We exploit this structure and obtain a variational problem in R 1 . Deriving its Euler–Lagrange equation yields a program with two unknowns, which can be solved quickly.